Comparison of Servqual Versus Ghost Shopping Measurement Methods : An Internal Control Instrument for Regional Banking towards Good Corporate Governance - Pifi Nugraheni, Jacika; Suwardi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Public Service is the main goal of governance. In the current era of globalization, people's needs and expectations are increasing andcomplex. This has fundamental consequences for business practices and public services, particularly the administration of RegionalOwned Enterprises, especially regional-owned banking. Regional-owned banking has a responsibility to contribute to increasingregional per capita income, and community self-reliance through products and services offered as a benchmark. success of regionalautonomy. Therefore, professional regional-owned banking management must be carried out by referring to the principles of GoodCorporate Governance. The role of service quality is an internal factor of support for the implementation of Good CorporateGovernance. This research departs from the many studies that have been conducted and published on the issue of Good CorporateGovernance, but only a few have discussed new approaches in measuring service quality that can be used as guidelines for companyinternal control instruments. This research method uses a mixed method which is more focused on aspects of the basic description ofqualitative measurements and the meaning of data from quantitative research results. The results showed that there were findings ofdata anomalies and significant differences in data between the servqual method and the ghost shopping customer method. Both ofthese methods have their limitations and advantages. The use of a combination of these methods can provide a more comprehensiveunderstanding of service quality.Keywords: Service Quality, Servqual, Ghost Shopping Customer, Good Corporate Governance